A pillar[5]arene-based cyanide sensor bearing on a novel cyanide-induced self-assemble mechanism. (April 2016) - Cheng, Xiaobin; Li, Hui; Zheng, Feng; Lin, Qi; Zhang, Youming; Yao, Hong; Wei, Taibao
Abstract: We have designed and synthesized a novel copillar[5]arene-based chemosensor, which employ 8-hydroxyquinoline group as a binding site and signal group. By a novel cyanide-induced self-assemble mechanism, the pillar[5]arene-based chemosensor shown high sensitivity and selectivity for cyanide in aqueous media. When cyanide was added to the solution of the chemosensor, a strong chartreuse fluorescence appeared. The detection limit of the fluorescent spectrum is 1.08 × 10 −8  mol L −1 for cyanide. Moreover, test strips based on the sensor were fabricated, the chemosensor is a good cyanide test kits. In addition, we made life applications of cyanide detected, the chemosensor is also could detect cyanide in aqueous extracts from sprouting potatoes. It is worth mentioning that cyanide-induced self-assemble mechanism is a novel strategy for the design of pillararene based chemosensor. Moreover, to the best of our knowledge, it's the first example of pillararene based cyanide chemosensors. Graphical abstract: A novel copillar[5]arenePQ5 is demonstrated to fluorescently sense CN − in aqueous media based on the mechanism of a novel cyanide-induced self-assemble. This work provides a novel approach for the selective recognition of CN − anions. Highlights: A novel copillar[5]arenePQ5 was synthesized for the sensor detection of CN − . A novel cyanide-induced self-assemble mechanism was proposed. The detection limits of the sensor for CN − were found to be 1.08 × 10 −8  mol L −1 . It's the first example of pillararene based cyanide chemosensors.